Midwifery Care for Pregnant Women With Low Back Pain Discomfort in Third Trimeter Pregnant Women in Clinics and Maternity Homes: Asuhan Kebidanan pada Ibu Hamil Dengan Ketidaknyamanan Nyeri Punggung Bawah Pada Ibu Hamil Trimeter III di Klinik dan Rumah Bersalin - Safitri, Eka Indi; Rusdyati, Tutik (Indonesian Journal of Innovation Studies, 2020)
Pregnancy is the period from the start of conception to the birth of the fetus, the duration is 280 days, counting from the first day of the last menstruation, pregnancy is the beginning of a new life in this period of life. During pregnancy the mother will find many changes both in terms of anatomy, physiology and even psychology so that it can be a cause of discomfort in pregnant women, while the discomfort of pregnancy in the third trimester experienced by women is low back pain which is a common complaint that often occurs in the majority of pregnant women, it is estimated about 70% in the third trimester. The purpose of this case study is to describe the discomfort of back pain that occurs in the third trimester at the delta pearl clinic and maternity home. The method used is a descriptive method which aims to create an objective picture with midwifery care that is used from assessment to evaluation. In the study of this case study, no complications were found, so there was no gap between discomfort and supporting theory.